Effect of Throat Washings on Detection of 2019 Novel Coronavirus - Wenliang Guo; Jiang Qian; Feng Ye; Shao-Qiang Li; Hong Cheng; Li-Yan Chen; Shi-yue Li (2020)
Abstract The 2019 novel coronavirus was detected in self-collected throat washings. The positive testing rate of throat washing was much higher than that of nasopharyngeal swabs. Throat washing is a promising candidate for 2019-nCoV screening and monitoring due to its noninvasiveness and reliability.